2009
DOI: 10.1016/j.neuron.2008.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Task Difficulty and Performance Induce Diverse Adaptive Patterns in Gain and Shape of Primary Auditory Cortical Receptive Fields

Abstract: Attention is essential for navigating complex acoustic scenes, when the listener seeks to extract a foreground source while suppressing background acoustic clutter. This study explored the neural correlates of this perceptual ability by measuring rapid changes of spectrotemporal receptive fields (STRFs) in primary auditory cortex during detection of a target tone embedded in noise. Compared to responses in the passive state, STRF gain decreased during task performance in most cells. By contrast, STRF shape cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
210
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(240 citation statements)
references
References 30 publications
27
210
3
Order By: Relevance
“…Although we cannot conclude that the neurophysiological response properties we have described here are necessarily essential for behavior, several existing studies using synthetic stimuli (34) and speech (23) have demonstrated that ferrets and rodents are able to perceive target sounds in noisy conditions similar to those used in this study. The functional properties observed for speech and conspecific vocalizations in distorted conditions may reflect computational strategies used in these behaviors, and future studies that combine our unique computational approach and behavior paradigms promise valuable new insight into the general problem of identifying signals in the background of interfering sources (5).…”
Section: Discussionmentioning
confidence: 65%
“…Although we cannot conclude that the neurophysiological response properties we have described here are necessarily essential for behavior, several existing studies using synthetic stimuli (34) and speech (23) have demonstrated that ferrets and rodents are able to perceive target sounds in noisy conditions similar to those used in this study. The functional properties observed for speech and conspecific vocalizations in distorted conditions may reflect computational strategies used in these behaviors, and future studies that combine our unique computational approach and behavior paradigms promise valuable new insight into the general problem of identifying signals in the background of interfering sources (5).…”
Section: Discussionmentioning
confidence: 65%
“…This subcortical tuning likely results from a dynamic feedback system that includes both sensory and cognitive mechanisms interacting via bottom-up and top-down mechanisms (23). The OPERA hypothesis is corroborated by animal work showing that sound-to-meaning associations drive neural plasticity (3,42,43) and that feedback from cortical areas is necessary for learningrelated plasticity in subcortical regions (44). Thus, we propose that in humans, cognitive skills, including attention, may drive experience-dependent neural plasticity for behaviorally meaningful stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, it has been successfully applied to neuroimaging data (Barnes et al, 2010;Rubinov and Sporns, 2011;Goulas et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as previous studies show that feature tuning in auditory cortex is highly affected by changes in task, context, and attention (Fritz et al, 2003;Atiani et al, 2009), the challenge for future work is to investigate changes in spectral profiles during these manipulations. Our results can guide future explorations of complex spectral tuning in human auditory cortex, and the methods described here provide a means for this endeavor.…”
Section: Neuronal Substrate Underlying Complex Population Tuningmentioning
confidence: 99%